Malignant transformation of recurrent juvenile laryngeal papilomatosis - Subramaniam, K.N.; Prepageran, Narayanan; Jalaludin, Mohd Amin; Krishnan, Gopala (Faculty of Medicine, University of Malaya, 2000)
[no abstract available]